A structural model of age, grey matter volumes, education, and personality traits. Issue 1 (3rd March 2015) - Kitamura, Soichiro; Yasuno, Fumihiko; Yamamoto, Akihide; Kazui, Hiroaki; Kudo, Takashi; Matsuoka, Kiwamu; Kiuchi, Kuniaki; Kosaka, Jun; Nagatsuka, Kazuyuki; Iida, Hidehiro; Kishimoto, Toshifumi
Abstract: Background: When the relationship between ageing and changes in personality traits is considered, it is important to know how they are influenced by biological and environmental factors. The present study examined the relationships between various factors associated with the effect of ageing on personality traits, including structural changes of the brain and environmental factors such as education. Methods: We recruited 41 healthy subjects. We administered the NEO Five‐Factor Inventory to assess personality factors. Magnetic resonance imaging was performed, and regional grey matter (GM) volumes were obtained. We identified associations in the correlation analysis of age, cerebral GM volume, years of education, and the personality trait of openness. Path analysis was used to estimate the relationships among these factors. Results: The path analysis model of age, GM volume, years of education, and the personality trait of openness revealed that age has an indirect negative association with openness through GM volume and years of education. Ageing was related to a decrease in GM volume, which was in turn related to a decrease in the openness score. Older subjects generally had fewer years of education, which was related to a lower openness score. Conclusions: Maintaining openness against the effects of ageing is desirable, and our results imply that interventions against age‐related cerebral atrophy and the promotion of opportunities for higher education may contribute to the development and stability of a healthy personality during the adult life course.